2006
DOI: 10.1021/es0516155
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Fouling of Submerged Membrane Bioreactors:  Impact of Mean Cell Residence Time and the Contributing Factors

Abstract: In this study, four bench-scale pre-anoxic submerged membrane bioreactors (MBR) were operated simultaneously at different mean cell residence times (MCRTs) (3, 5, 10, and 20 days) to systematically elucidate the contributing factors of membrane fouling. Severe membrane fouling was first observed in the 3-day followed by the 5-day MCRT MBRs. Minimal membrane fouling was detected in the 10 and 20-day MCRT MBRs. The fouling of microfiltration membrane was not controlled by mixed liquor suspended solids concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
101
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(106 citation statements)
references
References 28 publications
1
101
0
4
Order By: Relevance
“…The fouled membrane surface could have created an additional resistance for the soluble EPS to permeate the membrane. The passage of polysaccharides and proteins across the membrane could be at different rates, thereby resulting in different rejection efficiencies (Ng et al, 2006). This might be a possible cause.…”
Section: Characteristics Of Epsmentioning
confidence: 99%
See 2 more Smart Citations
“…The fouled membrane surface could have created an additional resistance for the soluble EPS to permeate the membrane. The passage of polysaccharides and proteins across the membrane could be at different rates, thereby resulting in different rejection efficiencies (Ng et al, 2006). This might be a possible cause.…”
Section: Characteristics Of Epsmentioning
confidence: 99%
“…Ahmed et al (2007), operating their MBRs at SRTs of 20, 60 and 100 d, found that membrane fouling at shorter SRTs was rapid and the fouling rate declined with an increasing SRT. Ng et al (2006) had also demonstrated that long SRT reduced the membrane fouling rate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MCRT controls the sludge growth rate and in many biological systems this is known to influence the production of extracellular polymeric (ECP) materials, which in turn may affect membrane fouling [7]. The current work did not investigate this or other microbiologically mediated factors that may contribute towards membrane fouling, but the importance of these and of the parameters controlling them should not be overlooked [7,22,28,29]. .…”
Section: 2mentioning
confidence: 96%
“…Soluble microbial products (SMP), which is believed identical to soluble EPS, are high molecular weight compounds released during cell lysis and cell growth, creating high resistance of the membrane and leading to a decline of permeate flux. Thus, investigation of EPS and SMP is an important issue in reducing membrane fouling in MBR [17,18]. However, there are only a few studies reporting process performance and investigation of EPS and SMP in the pre-denitrification MBR, especially for such system treating high-strength food wastewater.…”
Section: Introductionmentioning
confidence: 99%